Innovative use of fertilizers revives hope for Africa's Green Revolution - Busani Bafana (Africa Renewal, 2016)
Phillip Tshuma is a happy farmer. Despite one of the worst droughts ever to hit his country, Zimbabwe, Mr. Tshuma’s maize and small grains harvests this year are 50% more than they were in 2015, thanks to micro-dosing, the targeted application of small quantities of fertilizer in a field.